Hypertension and high ankle brachial index: the overlooked combination. Issue 1 (January 2019) - Alves-Cabratosa, Lia; Elosua-Bayes, Marc; García-Gil, Maria; Comas-Cufí, Marc; Martí-Lluch, Ruth; Ponjoan, Anna; Blanch, Jordi; Parramon, Dídac; Gomez-Marcos, Manuel Angel; Ramos, Rafel
Abstract : Objective: Assessment of asymptomatic organ damage in the management of hypertension includes low (<0.9) ankle brachial index (ABI) values. No recommendations are given for patients with high ABI (≥1.3), despite evidence of an association with increased risk. We aimed to study the association of high ABI with all-cause mortality and cardiovascular outcomes in a hypertensive population. Methods: In anonymized clinical records from the Catalan Primary Care (SIDIAP Q ) database, we designed a large cohort of hypertensive patients aged 35–85 years at the start date. Participants were excluded if they had previous heart failure, coronary heart disease, stroke, diabetes mellitus, or chronic kidney disease. The study population was categorized according to ABI values. Cox proportional hazards models were used to assess all-cause mortality, heart failure, acute myocardial infarction, and stroke. Results: From 2006 through 2015, SIDIAP Q records included 44 657 hypertensive patients with an ABI measurement 9126 of whom met inclusion criteria. The median follow-up (first to third quartiles) was 6.0 years (4.7–7.6). High ABI (≥ 1.3) was associated with an increase in mortality risk, hazard ratio, and 95% confidence interval: 1.44 (1.10–1.88), similar to the group with ABI at least 0.9 and less than 1.1, hazard ratio 1.36 (1.12–1.65), and lower than all groups with ABI less than 0.9. High ABI values tended to associate with heart failure, hazard ratio 1.34 (0.95–1.91), but the relation of high ABI with acute myocardial infarction and stroke was nonsignificant, hazard ratios 1.30 (0.72–2.35) and 0.97 (0.65–1.42), respectively. Conclusion: Patients with high ABI values and hypertension presented an increased all-cause mortality risk that could be considered when advising such patients. Abstract : Supplemental Digital Content is available in the text